Ovarian tissue cryopreservation and transplantation in patients with cancer - Sooyoung Kim; Younji Lee; Sanghoon Lee; Tak Kim (Korean Society of Obstetrics and Gynecology, 2018)
Chemotherapy and radiotherapy improved survival rates of patients with cancer. However, they can cause ovarian failure and infertility in women of reproductive age. Infertility following cancer treatment is considered a major quality of life issue. Ovarian tissue cryopreservation and transplantation is an important option for fertility preservation in adult patients with cancer who need immediate chemotherapy or do not want to undergo ovarian stimulation. Ovarian tissue freezing is the only option for preserving the fertility of prepubertal patients with cancer. In a recent review, it was reported that frozen-thawed ovarian transplantation has lead to about 90 live births and the conception rate was about 30%. Endocrine function recovery was observed in 92.9% between 3.5 and 6.5 months after transplantation. Based on our review, ovarian tissue cryopreservation and transplantation may be carefully considered before cancer treatment in order to preserve fertility and endocrine function in young cancer survivors.